If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6q = 30q Solving 6q = 30q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-30q' to each side of the equation. 6q + -30q = 30q + -30q Combine like terms: 6q + -30q = -24q -24q = 30q + -30q Combine like terms: 30q + -30q = 0 -24q = 0 Divide each side by '-24'. q = 0 Simplifying q = 0
| y^5-2y^3+y=0 | | 6(3-2x)=42 | | 4(7r+3)=236 | | x+7+x+7-17=17 | | x+7+x+7-17=11 | | 3ln(2x-5)=6 | | 4x^2+8=72 | | 3ln(2x+5)=6 | | 8x-2=6x+12 | | 6x+6+2x=24 | | 36-(-4)= | | 7+x+7-17=11 | | 27=7+9+C | | -19+-2= | | 11x+12-3x=30 | | 27=7 | | bx+d=a | | 7x-2=90 | | q^2+2q-16=0 | | 5x-4=4-d | | -42+-12= | | 35=7+12+C | | 4+17x=56 | | 6x+10=90 | | 8+x=56 | | 9t-18t=-18 | | 3(-2r-2)=-2(3r+3) | | 10x-2=8x+6 | | 13+-13= | | cy+by-cz-bz= | | (-6)2*(-6)5= | | 144=4*8*4+2*4*W |